Time : a user's guide - Klein, Stefan, 1965-; Frisch, Shelley Laura (London : Penguin, 2008)
Stefan Klein explores the hidden dimensions of time, looking at everything from when the present becomes the past to the tribe that see the future backwards, from when sex is best to why the years seem to speed by as we age.
This translation originally published: New York: Marlowe, 2007.
Includes bibliographical references (pages 301-316) and index.
Translated from the German.
A wide ranging description on issues of time in science and society. Translated from the German 2006 edition
Keywords: Time perception; Time -- Social aspects; time; Sociology